Investigation of the mechanical behavior of a graded cellular rod under impact - Tang, Irving Wei Han. (2013)
This report documents the investigation of the behavior and the underlying mechanism of cellular rod with graded cross-sectional area under dynamic loading. Theoretical finite element (FE) simulations and physical experiments were carried out for comparison.